The Use of the PBL (Problem Based Learning) Model in the Material of Matter and Object Form to Improve Critical Thinking Skills and Student Learning Outcomes - Alamha; Sukendro; Indryani (Postgraduate, University of Mataram, 2025)
PBL (Problem-Based Learning) teaching with problem-based skills is effective for improving learning through critical thinking activities and enhancing learning outcomes. Critical thinking is logical and reflective thinking that focuses on deciding what should be believed or done. This study is classroom action research aimed at improving students' critical thinking skills and learning outcomes by using the PBL (Problem Based Learning) model in the material of matter and its states. Data were collected using observation sheets and evaluation questions at the end of each cycle. Critical thinking skills data were obtained by summing all scores across 5 indicators, dividing by the total maximum score, then multiplying by 100. The score obtained was 49, which met the criteria for sufficient critical thinking in cycle I, and increased to 63, meeting the criteria for critical thinking in cycle II. The percentage of learning mastery increased from 11% in the pre-cycle to 66.7% in cycle I, and further increased to 83% in cycle II. This proves that the use of PBL (Problem Based Learning) can enhance students' critical thinking skills and learning outcomes.